The humanitarian displacement in Ecuador and the migratory processes in its border zone: Vulneration or right - Luque González, Arturo (2019)
The present article has as objective the historical analysis of the violation of the rights of the victims of the migratory displacement towards Ecuador: its beginnings, evolution, and current perspective, in relation to the tensions that have been generated in the last times because of the great overflow and income of Venezuelan citizens, due to unemployment and problems within the context of their country of origin. It includes a normative framework that regulates the migratory flows of both countries.